Metabolomic Profiling LC-MS Based Bioactive Compound of Sonneratia alba, Antioxidant Activities and Its In-silico molecular docking Studies - Tarigan, Indra Lasmana; Latief, Madyawati; Anshori, Jamaludin Al; Melani, Fitria; Putri, Silvi Ayudiah; Husna, Naimul; Warni, Tri; Ramadhan, Ilham Ifandi; Yusnaidar, Yusnaidar; Sutrisno, Sustrisno (Molekul, 2025)
ABSTRACT. Mangrove Perepat (Sonneratia alba) plants have various potentials that need to be utilized optimally because they have varying bioactive compound content. A comprehensive exploration of secondary metabolite compound content and plant bioactivity based on metabolomics and in-silico molecular docking is needed to see the effects of single or multiple compounds. This study aimed to obtain a profile of medicinal compounds from Perepat leaves as antioxidants. Extraction was carried out using five gradients of Ethanol: Water concentration. EP1 (water), EP2 (25% Ethanol), EP3 (50% Ethanol), EP4 (75% Ethanol), EP5 (100% Ethanol). The research was carried out through extraction, antioxidant determination, metabolomics, and molecular docking. Exploration data showed that increasing ethanol concentration increased phenolics, flavonoids, and antioxidant activity. EP5 has the highest total phenolics and flavonoids of 24.978 mgGAE/g and 42.97 mgQE/g, respectively, with an IC50 value of 8.263 ppm. Docking analysis of 37 test compounds identified 12 compounds with low binding energy, ranging from -7 to -9 kcal/mol, with the NADPH oxidase protein receptor (PDB ID: 2CDU). These compounds include kaempferol-3-rhamnoside, meperidine, apigenin-7-O-glucoside, 2-keto benzothiazole 54, methyl propanoic acid, salicyloylaminotriazole, salicylihalamide A, and gibberellin A7. Our findings suggest that S. alba extract holds potential for further exploration as a natural antioxidant source. Keywords: Antioxidant; In-silico; Metabolomics; S. alba